The Management of Chemosis after Blepharoplasty - Ní Dhubhghaill, Sorcha; Faris, Callum (Facial Plastic Surgery, 2022)
Chemosis is a common, though typically temporary complication of both upper and lower blepharoplasty surgery, though it is much more common after the latter. It occurs due to extravasation of fluid into the subconjunctival space precipitated by desiccation, inflammation, and manipulation of the conjunctiva and associated lymphatic drainage. Intraoperatively, minimizing surgical exposure and manipulation as well as maintaining a moist ocular surface can reduce the risks. Postoperatively, we propose a stepwise approach, starting with lubricants and escalating to increasingly potent anti-inflammatories with compression bandaging and surgery reserved for persistent cases.
Keywords: chemosis; conjunctiva; blepharoplasty